Digte - Andersen, Hans Christian (Trykt, paa Forfatterens Forlag, hos C. H. Robert, 1830)
Saturs: Digte ; Dödningen, et fyensk folke-eventyr. Fraktūras burti.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature; Dāņu dzeja; Dāņu literārās pasakas; Literārās pasakas, dāņu; Danish poetry; Danish literary tales; Literary tales, Danish